Pharmacogenetics of antiepileptic drug efficacy in childhood absence epilepsy. Issue 3 (March 2017) - Glauser, Tracy A.; Holland, Katherine; O'Brien, Valerie P.; Keddache, Mehdi; Martin, Lisa J.; Clark, Peggy O.; Cnaan, Avital; Dlugos, Dennis; Hirtz, Deborah G.; Shinnar, Shlomo; Grabowski, Gregory; ,
Abstract : Objective: To determine whether common polymorphisms in CACNA1G, CACNA1H, CACNA1I, and ABCB1 are associated with differential short‐term seizure outcome in childhood absence epilepsy (CAE). Methods: Four hundred forty‐six CAE children in a randomized double‐blind trial of ethosuximide, lamotrigine, and valproate had short‐term seizure outcome determined. Associations between polymorphisms (minor allele frequency ≥ 15%) in 4 genes and seizure outcomes were assessed. In vitro electrophysiology on transfected CACNA1H channels determined impact of 1 variant on T‐type calcium channel responsiveness to ethosuximide. Results: Eighty percent (357 of 446) of subjects had informative short‐term seizure status (242 seizure free, 115 not seizure free). In ethosuximide subjects, 2 polymorphisms ( CACNA1H rs61734410/P640L, CACNA1I rs3747178) appeared more commonly among not–seizure‐free participants ( p = 0.011, odds ratio [OR] = 2.63, 95% confidence limits [CL] = 1.25–5.56; p = 0.026, OR = 2.38, 95% CL = 1.11–5.00). In lamotrigine subjects, 1 ABCB1 missense polymorphism (rs2032582/S893A; p = 0.015, OR = 2.22, 95% CL = 1.16–4.17) was more common in not–seizure‐free participants, and 2 CACNA1H polymorphisms (rs2753326, rs2753325) were more common in seizure‐free participants ( p = 0.038, OR = 0.52, 95% CL = 0.28–0.96). In valproate subjects, no common polymorphisms were associated with seizure status. In vitro electrophysiological studies showed no effect of the P640L polymorphism on channel physiology in the absence of ethosuximide. Ethosuximide's effect on rate of decay of CaV 3.2 was significantly less for P640L channel compared to wild‐type channel. Interpretation: Four T‐type calcium channel variants and 1 ABCB1 transporter variant were associated with differential drug response in CAE. The in vivo P640L variant's ethosuximide effect was confirmed by in vitro electrophysiological studies. This suggests that genetic variation plays a role in differential CAE drug response. Ann Neurol 2017;81:444–453